Virtual reality in language learning: a systematic review and implications for research and practice - Parmaxi, Antigoni (Interactive learning environments, 2023)
The increasing popularity of Virtual Reality (VR) has provoked scholars' and educators' interest to explore its potential as a learning environment for various fields of education. Along this line, several literature reviews have analysed and synthesised the educational use of VR; however, scholar activity is lacking a recent review of VR on a specific field of interest such as language learning. Thus this paper delineates the contour of scholarly literature on VR as an emerging technology in language teaching and learning. Using 17 high-impact journals and conferences in the fields of Computer-Assisted Language Learning and Educational Technology as a source, 26 scholarly manuscripts were retrieved from 2015 to 2018, analysed and synthesised under the following foci: (a) technologies used, language learning settings and duration of educational activities; (b) benefits and limitations from using VR as an educational tool in the language classroom; (c) future research directions regarding the educational use of VR based on the reviewed literature. This paper argues that VR is an invaluable tool in the language classrooms but entails challenges regarding its technical configuration, as well as its pedagogical grounding. The study concludes with some discussion and implications for researchers and practitioners.